Modelling human diabetes ex vivo: a glance at maturity onset diabetes of the young - Ka, Moustapha; Hawkins, Eleanor; Pouponnot, Celio; Duvillié, Bertrand (Frontiers in Endocrinology, 2024)
Diabetes is a complex metabolic disease which most commonly has a polygenic origin; however, in rare cases, diabetes may be monogenic. This is indeed the case in both Maturity Onset Diabetes of the Young (MODY) and neonatal diabetes. These disease subtypes are believed to be simpler than Type 1 (T1D) and Type 2 Diabetes (T2D), which allows for more precise modelling. During the three last decades, many studies have focused on rodent models. These invesQgaQons provided a wealth of knowledge on both pancreas development and beta cell funcQon. In parQcular, they allowed the establishment of a hierarchy of the transcripQon factors and highlighted the role of microenvironmental factors in the control of progenitor cell proliferaQon and differenQaQon. Transgenic mice also offered the possibility to decipher the mechanisms that define the funcQonal idenQty of the pancreaQc beta cells. Despite such interest in transgenic mice, recent data have also indicated that important differences exist between mice and human. To overcome these limitaQons, new human models are necessary. In the present review, we describe these ex vivo models, which are created using stem cells and organoids, and represent an important step toward islet cell therapy and drug discovery.